Do Future Limitation Perspective in Cancer Patients Predict Fear of Cancer Recurrence, Mental Distress, and the Ventromedial Prefrontal Cortex Activity? - Zhou, Jia; Feng, Pan; Lu, Xiaofei; Han, Xingping; Yang, Yanli; Song, Jingjing; Jiang, Guangyu; Zheng, Yong (Frontiers in Psychology, 2018)
Life-threatening diseases (e.g., cancer) affect people's future time perspective, and affect their mental health. When one’s lifetime is perceived as running out, the individual is possessing a future limitation perspective (FLP), and which is one of factors in future time perspective. In this study, we explored the structural relationship between FLP, fear of cancer recurrence (FCR), mental health status (MHS), and brain activity in patients with cancer. Cancer patients were divided into two groups using the Future Time Perspective scale and Feelings About Life scale: a strong FLP group (S-FLP) and a weak FLP group (W-FLP). For these groups, we measured cancer patients’ MHS using the Symptom Checklist (SCL-90) and FCR using the Cancer Acceptance Scale; brain activity was measured using resting-state functional magnetic resonance imaging (rs-fMRI). Behavioural results showed that the S-FLP group had higher mental symptom and FCR scores than did the W-FLP group. Neuroimaging results revealed that spontaneous brain activity in the ventromedial prefrontal cortex (vmPFC) was stronger in the W-FLP group than in the S-FLP group. Moreover, brain activity in the vmPFC was negatively correlated with FLP, FCR, and SCL-90 scores only in the S-FLP group, and the model constructed further indicated that FCR and SCL-90 scores fully mediated the relationship between FLP and vmPFC activities. These findings suggested that a strong FLP might lead to mental disorders and greater FCR, which might change the spontaneous activity of the vmPFC in cancer patients.